A most ingenious paradox : the art of Gilbert and Sullivan - Wren, Gayden, 1961- (Oxford University Press, 2001)
Written more than a century ago, and initially regarded even by their creators as nothing more than light entertainment, the operas of Gilbert and Sullivan emerged over the course of the 20th century as the world's most popular body of musical-theatre works. Despite the works' resounding popularity and proven longevity however, most books written on Gilbert and Sullivan have focused on the authors, rather than their work. Examining all fourteen operas in detail, Gayden Wren offers a fresh look at the works themselves. He argues that the key to the operas' longevity lies not primarily in their clever lyrics, witty dialogue, or catchy music, but in the central themes underlying the characters and stories.